LITERARY ECOLOGY STUDY NOVEL JERIT RINDU DARI LENGKO BUKIT KOMBA FOR THE RESCUE AND PRESERVATION OF THE NATURAL ENVIRONMENT IN MANGGARAI - Agatha Trisari Swastikanthi (Prosiding Seminar Nasional dan Internasional HISKI, 2021)
Nature and man work together to take care of each other. However, the nature of man causes an imbalance between the two because man utilizes and exploits natural wealth for his benefit. The purpose of the study is to uncover manganese mining exploitation activities in Bukit Rengge Manggarai. This research method is qualitatively descriptive. The data source is the text of the novel Jerit Rindu dari Lingko Bukit Rengge Komba by Endang Moerdopo. The analysis results showed that the people of Manggarai were aware of the adverse effects of mangan mining activities in their area.  Their struggle was successful, even though many people were victims. The local government followed up the community's request by making policies to preserve the natural environment in Bukit Range Manggarai NTT.